2019
DOI: 10.1101/851980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Native mass spectrometry can effectively predict PROTAC efficacy

Abstract: Protein degraders, also known as proteolysis targeting chimeras (PROTACs), are bifunctional small molecules that bring an E3 ubiquitin ligase and a protein of interest (POI) into proximity, thus promoting ubiquitination and degradation of the targeted POI [1-3]. Despite their great promise as next-generation pharmaceutical drugs, the development of new PROTACs is challenged by the complexity of the system, which involves binary and ternary interactions between components. Here, we demonstrate the strength of n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Assays other than the aforementioned that have also been used to characterize ternary complexes include size exclusive chromatography (SEC) [94,95], crystallography [25,35,74], co-immunoprecipitation (Co-IP) [83,96], mass spectrometry (MS) [61,97] and the NanoBiT R assay [95].…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Assays other than the aforementioned that have also been used to characterize ternary complexes include size exclusive chromatography (SEC) [94,95], crystallography [25,35,74], co-immunoprecipitation (Co-IP) [83,96], mass spectrometry (MS) [61,97] and the NanoBiT R assay [95].…”
Section: Othersmentioning
confidence: 99%
“…MS is another label-free technique that can provide insights into PROTAC degrader-mediated PPI [61,97]. According to the study by Beveridge et al, native MS can preferentially reveal the E3-PROTAC-POI ternary complex in competition experiments with multiple substrate proteins present, thereby suggesting that it is not only an ideal HTS strategy for the development of new PROTACs [97] but also a valuable tool to dissect the mechanism of actions, selectivity and specificity of PROTACs.…”
Section: Othersmentioning
confidence: 99%
“…used native nano‐ESI‐Q‐TOF‐MS to effectively study PROTAC‐mediated protein complexes in a label‐free manner. The use of native MS was demonstrated to be capable of the characterization of PROTAC‐protein complexes, semi‐quantification of their equilibria, insight into PROTAC specificities for substrate proteins and PROTAC cooperativity, and competitive experiments 40 . This work highlights the potential of native‐HRMS for high‐throughput methods in PROTACs development.…”
Section: Hrms Applications In 2020mentioning
confidence: 93%
“…Protein degraders, commonly known as proteolysis targeting chimeras (PROTACs), are small molecule inhibitors that block the activities of intracellular target proteins and interfere with signaling pathways 39,40 . This is an emerging modality that has seen limited growth due to the complexities of the PROTAC‐mediated protein interactions that involve binary and ternary interactions between the components 39,40 . Beveridge et al .…”
Section: Hrms Applications In 2020mentioning
confidence: 99%
“…[28][29][30] (However, it has recently been suggested that such covalent binders are perhaps ill-suited for PROTACs, 31,32 although this finding has itself been questioned. 33 ) Multiple independent research groups have recently developed photoactivated PROTACs, [34][35][36][37] and novel experimental diagnostic techniques [38][39][40] will continue to afford additional insight with both greater accuracy and throughput.…”
Section: Introductionmentioning
confidence: 99%